A ghost tale for christmas time eaudiobook - Osborne, Mary Pope (Magic Tree House: Merlin Missions, 2010)
Magic. Mystery. Time-travel. Join Jack, Annie and the Magic Tree House in this historical holiday story that puts a twist on Charles Dicken's classic The Christmas Carol —from the #1 bestselling chapter book series of all time! Jack and Annie must help the famous writer Charles Dickens! The brother and sister are whisked back in time to Victorian England and the foggy streets of London. There, Jack and Annie discover that Charles Dickens has been thrown in jail! How can they help him? They will need all their magic-and help from three ghosts-to keep the great writer from ruining his life! Formerly numbered as Magic Tree House #44, the title of this book is now Magic Tree House Merlin Mission #16: A Ghost Tale for Christmas Time. The Merlin Missions books are more challenging adventures that will delight experienced readers who are fans of the original chapter book series! The Magic Tree House series has been a favorite for over 25 years and is sure to inspire a love of reading—and adventure—in every child who joins Jack and Annie! Did you know that there’s a Magic Tree House book for every kid? • Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books • Magic Tree House Graphic Novels:  Jack and Annie's original adventures come to life with full-color, vibrant art, perfect for graphic novel fans and reluctant readers • Merlin Missions: More challenging adventures for the experienced reader • Super Edition: A longer and more dangerous adventure • Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures